IJE 2022
DOI: 10.55362/ije/2022/3661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Application of Micronutrients on Yield and Economics of Ginger under Eastern Ghat High Land Zone of Odisha

Abstract: A study was conducted in Eastern Ghat High Land Zone of Odisha to explore the effect of foliar application of micronutrients on ginger during 2017-18 to 2019-20.The treatments consisted of three cultivars viz. V1 (Supranha), V2 (Suravi) and V3 (Varada) and foliar application of IISR ginger micronutrients @ 5 g/litre of water at 60 and 90 days after planting. Ginger variety Suravi was superior over other varieties in terms of yield and economics. Application of micronutrient showed significant variation for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In the cultivation of medicinal plants, micro-fertilizers are commonly used to enhance both yield and bioactive substance content. Trace elements are essential nutrients for plant growth, and although the demand for them is relatively small, each trace element plays an important biological role ( Parshuram, Himangshu & Ranjan, 2022 ; Xiaodong et al, 2022 ). It has been reported that the application of micro-fertilizer (0.2% B, 0.3% Cu, 0.8% Fe, 0.4% Mn, 0.3% Zn) can increase the umbel number, seed yield per plant and per decare, thousand seed weight, as well as the essential oil content of anise ( Pimpinella anisum ) ( Günay & Gümüşçü, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the cultivation of medicinal plants, micro-fertilizers are commonly used to enhance both yield and bioactive substance content. Trace elements are essential nutrients for plant growth, and although the demand for them is relatively small, each trace element plays an important biological role ( Parshuram, Himangshu & Ranjan, 2022 ; Xiaodong et al, 2022 ). It has been reported that the application of micro-fertilizer (0.2% B, 0.3% Cu, 0.8% Fe, 0.4% Mn, 0.3% Zn) can increase the umbel number, seed yield per plant and per decare, thousand seed weight, as well as the essential oil content of anise ( Pimpinella anisum ) ( Günay & Gümüşçü, 2023 ).…”
Section: Introductionmentioning
confidence: 99%